2011
DOI: 10.1007/s00442-011-2042-9
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites and nutrients of woody plants in relation to browsing intensity in African savannas

Abstract: Carbon-based secondary metabolites (CBSMs) are assumed to function as 26 defences that contribute to herbivore-avoidance strategies of woody plants. Severe 27 browsing has been reported to reduce concentrations of CBSMs and increase N 28 concentrations in individual plants, causing heavily browsed plants to be characterised 29 by N-rich/C-poor tissues. We hypothesised that concentrations of condensed tannins 30 (CT) and total polyphenols (TP) should decrease, or N increase, in relation to 31 increasing int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 54 publications
2
55
0
Order By: Relevance
“…The positive relationship we observed between browsing intensity and [N] supports our hypothesis, as does the negative relationship between browsing intensity and [CT], which corroborates observations of other deciduous, spineless species that are well endowed with CTs, e.g. Combretum apiculatum (Rooke and Bergström 2007;Scogings et al 2011). However, our results contradict observations of C. mopane, which is another deciduous, spineless, CT-rich species heavily used by elephants (Wessels et al 2007;Hrabar et al 2009).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The positive relationship we observed between browsing intensity and [N] supports our hypothesis, as does the negative relationship between browsing intensity and [CT], which corroborates observations of other deciduous, spineless species that are well endowed with CTs, e.g. Combretum apiculatum (Rooke and Bergström 2007;Scogings et al 2011). However, our results contradict observations of C. mopane, which is another deciduous, spineless, CT-rich species heavily used by elephants (Wessels et al 2007;Hrabar et al 2009).…”
Section: Discussionsupporting
confidence: 88%
“…The site was also readily accessible by road. Sampling was scheduled according to observations in similar environments elsewhere, which indicated that effects of browsing on chemistry of mature leaves is readily detectible in the latter half of the wet season (Scogings et al 2011). Sampling only mature leaves at one time ensured that leaf phenology would not confound our results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings lend strong support to this notion as the most heavily structurally defended species ( A. etbaica and B. pedicellaris ) performed the best in the presence of herbivores despite low investments in N‐free secondary metabolites. However, Scogings et al () predicted that the concentrations of N‐free secondary compounds would depend on browsing intensity with the highest concentrations occurring at intermediate levels of browsing for certain functional groups. For example, Scogings et al (), predict a linear increase in N‐free secondary compounds with browsing intensity, with a potentially sudden decrease at very high levels of browsing pressure in deciduous savanna species.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical defences on the other have been found to be down‐regulated by herbivory in savannas, most likely due to C‐limitation imposed by the repeated removal of photosynthesising leaf material by browsing herbivores (e.g. Scogings, Hjältén, & Skarpe, , ; Scogings, Mamashela, & Zobolo, ; Wigley et al, ). It is, however, still not clear if similar plant functional types (e.g.…”
Section: Introductionmentioning
confidence: 99%